Design and Feasibility of EXE Learning Media on the Topic of Chemical Bonding - Djoa, Dominikus Djago; Kusumaningtyas, Pintaka (International Journal of Active Learning, 2021)
The transformation on the industrial era 4.0 has greatly influenced changes in the way students learn who are more dominantly use gadgets both online and offline. This research aims to develop an e-Learning XHTML Editor (EXE) learning media which is feasible to be used in chemistry learning on the topic of Chemical Bonding, and also to test the validity and practicality of the media. The study used a research and development (R & D) design by adapting Hannafin and Peck’s model. The steps are limited to the design of EXE learning media. The feasibility of the EXE learning media is tested in terms of validity and practicality. The instrument used are validation questionnaire and students’ response questionnaire. The data were obtained and analyzed by using descriptive percentage. The results of the feasibility test conducted by the material experts, media experts, and teachers obtained an average of 89% with very feasible category. Meanwhile, the practicality test was obtained from the results of students’ response questionnaire from SMAN 8 Samarinda and SMAN 3 Tenggarong, showing the practicality value is 87% with the category of very practice and easy to operate and useful. It means the EXE learning media is feasible and practice to be used as chemistry learning media on the topic of Chemistry Bonding.